Reconstructing science networks from the past: Eponyms between malacological authors in the mid-19th century - Breure, Abraham S.H.; Heiberger, Raphael Heiko (Journal of Historical Network Research, 2019)
Reconstructing scientific networks from the past can be a difficult process. In this paper, we argue that eponyms are a promising way to explore historic relationships between natural scientists using taxonomy. Our empirical case is the emerging community of malacologists in the 19th century. Along the lines of pivotal concepts of social network analysis we interpret eponyms as immaterial goods that resemble the proporties of regular social contacts. Utilising Exponential Random Graph Models reveals that the social exchange underlying eponyms follows similar rules as other social relationships such as friendships or collaborations. It is generally characterized by network endogenous structures and homophily. Interestingly, the productivity of authors seems to be well recognised among contemporary researchers and increases the probability of a tie within the network significantly. In addition, we observe an epistemological divide in the malacological research community. Thus even in the 19th century, at a time when science was just emerging as a differentiated social system, epistemological distinctions have been a defining concept for scientific contacts.